Pengaruh Pemberian Madu terhadap Penurunan Frekuensi Batuk Pada Anak di RSIA Sitti Khadijah Kota Gorontalo - Modjo, Dewi; Sudirman, Andi Akifa; Rias, Rianti U (Universitas Malahayati, 2024)
ABSTRACT Coughing in children, if it cannot be done above, can cause blockages in the airways and cause more serious problems such as severe tightness to death due to blockages in the airways due to the large amount of sputum production during coughing, so to prevent this, honey can be given to reduce the frequency of coughing. This study aims to analyze the effect of honey administration on reducing cough frequency in children at RSIA Sitti Khadijah, Gorontalo City. This study aims to analyze the effect of honey administration on reducing cough frequency in children at RSIA Sitti Khadijah, Gorontalo City. This study is a quantitative research using a One group pre-test and post-test design design that provides treatment or intervention to the research subject and then the effect of the treatment is measured and analyzed. This sampling uses purposive sampling with a total of 15 samples. The results of the analysis of the average frequency of children's cough before being given honey was 10.33 with a standard deviation of 2.636 and the average frequency of children's cough after being given honey was 5.73 with a standard deviation of 1.223, and a p-value of 0.000 which means that there was an effect of honey administration on the reduction of cough frequency in children at RSIA Sitti Khadijah, Gorontalo City. Keywords: Children, Cough Frequency, Honey ABSTRAK Batuk pada anak apabila tidak dapat diatas dapat mengakibatkan sumbatan pada jalan nafas dan menimbulkan masalah yang lebih berat seperti sesak yang hebat hingga kematian akibat sumbatan pada jalan nafas karena banyaknya produksi sputum saat batuk sehingga untuk mencegah hal tersebut dapat diberikan madu untuk mengurangi frekuensi batuk. Penelitian ini bertujuan untuk menganalisis pengaruh pemberian madu terhadap penurunan frekuensi batuk pada anak di RSIA Sitti Khadijah Kota Gorontalo. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan desain One group pre-test and post-test design yang memberikan perlakuan atau intervensi pada subyek penelitian kemudian efek perlakuan tersebut diukur dan dianalisis. Pengambilan sampel ini menggunakan purposive sampling dengan jumlah 15 sampel. Hasil analisis rata-rata frekuensi batuk anak sebelum diberikan madu adalah 10,33 dengan standar deviasi 2,636 dan rata-rata frekuensi batuk anak sesudah diberikan madu adalah 5,73 dengan standar deviasi 1,223, serta p-value 0,000 yang artinya ada pengaruh pemberian madu terhadap penurunan frekuensi batuk pada anak di RSIA Sitti Khadijah Kota Gorontalo. Kata Kunci: Anak, Frekuensi Batuk, Madu